Long‐term effects of litter sex ratio on female reproduction in two iteroparous mammals. (20th January 2014) - Monclús, Raquel; von Holst, Dietrich; Blumstein, Daniel T.; Rödel, Heiko G.; Blount, Jonathan
Summary Female mammals that develop in male‐biased litters show signs of masculinization because they are exposed to the testosterone produced by their male siblings in utero. The early exposure to testosterone can affect female morphology, physiology, behaviour and life‐history traits. Masculinization is commonly seen as the collateral effect of developing in a male‐biased litter. However, when resources are limiting, masculinization might be adaptive because androgenized females could monopolize resources. We investigated whether females from male‐biased litters, and therefore likely to be masculinized, showed adaptive advantages under different competing scenarios. For that, we used data from two long‐term field projects studying yellow‐bellied marmots (Marmota flaviventris Audubon and Bachman, 1841) and European rabbits (Oryctolagus cuniculus Linnaeus, 1758). We explored whether litter sex composition affected fitness‐related reproductive traits: the onset of breeding, offspring production and the probability of reproduction in a given year. Our study shows long‐term consequences of litter sex composition on reproduction in European rabbits and yellow‐bellied marmots. Females from male‐biased litters from both species delayed the onset of breeding, suggesting the maladaptive nature of masculinization. However, in European rabbits, this effect was density‐dependent. Under higher‐density conditions, female rabbits from male‐biased litters brought forward the onset of breeding, which might increase the probability of offspring overwinter survival and therefore their fitness. These females under limiting conditions might have a higher resource holding potential. We conclude that prenatal maternal effects in natural populations should be taken into account when studying life‐history variation. Moreover, it is notable that small variations in naturally occurring prenatal exposure to androgens have profound impacts on individuals, social groups and the population structure.